EFFECTIVE HOMEWORK PRACTICES IN MODERN EDUCATION SYSTEMS - Sharofat Pakirdinova Abdumutaljonovna; Abdurakhimova Gulchiroy (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
Homework is crucial in contemporary education frameworks, but its success is largely contingent on its design and execution. This research examines successful homework strategies and their influence on student academic performance. Employing a mixed-methods strategy, information was gathered from educators and learners via surveys and observations in the classroom. The results indicate that thoughtfully designed, intentional, and appropriately challenging assignments greatly improve student involvement, comprehension, and self-directed learning abilities. Conversely, overly burdensome or inadequately structured tasks can result in reduced enthusiasm and educational pressure. The conversation emphasizes the significance of matching homework with teaching objectives and student requirements, along with offering prompt feedback. In general, the research indicates that well-planned and consistently implemented homework strategies can enhance educational results